2017
DOI: 10.1007/s10955-017-1906-8
|View full text |Cite
|
Sign up to set email alerts
|

Using Perturbed Underdamped Langevin Dynamics to Efficiently Sample from Probability Distributions

Abstract: In this paper we introduce and analyse Langevin samplers that consist of perturbations of the standard underdamped Langevin dynamics. The perturbed dynamics is such that its invariant measure is the same as that of the unperturbed dynamics. We show that appropriate choices of the perturbations can lead to samplers that have improved properties, at least in terms of reducing the asymptotic variance. We present a detailed analysis of the new Langevin sampler for Gaussian target distributions. Our theoretical res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…l Proof of Theorem 1. 3 We write the generator of the Stratonovich-perturbed dynamics as L S "´B 7 BÁ 7 A with B " ∇, A " g¨∇, A 7 "´A. The quadratic form associated to L S is x´L S φ, φy π " }Bφ} 2 π`} Aφ} 2 π for all φ P H 1 pπq the weighted Sobolev space that is defined in the standard manner.…”
Section: Proof Of the Main Resultsmentioning
confidence: 99%
“…l Proof of Theorem 1. 3 We write the generator of the Stratonovich-perturbed dynamics as L S "´B 7 BÁ 7 A with B " ∇, A " g¨∇, A 7 "´A. The quadratic form associated to L S is x´L S φ, φy π " }Bφ} 2 π`} Aφ} 2 π for all φ P H 1 pπq the weighted Sobolev space that is defined in the standard manner.…”
Section: Proof Of the Main Resultsmentioning
confidence: 99%
“…Another work [8,18] only analyzed skew acceleration for LD. A previous work [17] combined a non-reversible drift term with ULD. Unlike our method, this work's purpose was to reduce the asymptotic variance of the expectation of a test function and is mainly focusing on sampling from Gaussian distribution.…”
Section: Relation To Non-reversible Methodsmentioning
confidence: 99%
“…For example, skew acceleration has been analyzed focusing on sampling from Gaussian distributions [13][14][15][16][17], although assuming Gaussian distributions in Bayesian models is restrictive in practice. A recent study [8] theoretically showed that skew acceleration accelerates the dynamics around the local minima and saddle points for non-convex functions.…”
Section: Introductionmentioning
confidence: 99%
“…. , n, J i ∈ R d×d skew being skew-symmetric matrices and Q i : R d → R d×d sym being positive definite matrix-valued functions, as discussed in [28,Section 2]. Note that in this case the processes (X i t ) t≥0 are not copies of each other, since Q i and J i may not be the same for different particles.…”
Section: The General Casementioning
confidence: 99%
“…Remark 29. Generalising the above to the case where the particles have different frictions γ i and masses M i or some or all of them move according to perturbed versions of underdamped Langevin dynamics as considered in [28] is straightforward (see also Remark 24).…”
Section: Underdamped Langevin Dynamicsmentioning
confidence: 99%